Kinematic analysis of javelin release characteristics - a case study - Mlanovic, D.; Mejovsek, M.; Hraski, Z. (1998)
The author compares a javelin throw of one of the best Croatian javelin throwers with data gathered for the eleven 1992 Olympic finalists.